THE ROLE OF SOCIAL MEDIA AS A SOURCE OF COVID-19 VACCINATION INFORMATION - Muhamad Reznu Firsyawardana; Sunarto Sunarto (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2022)
This research is based on the implementation of a national vaccination campaign to prevent the transmission of Covid-19 in Indonesia, and the presence of social media can shorten the government's target in achieving the national target of 181.5 million people in Indonesia. This study uses qualitative research with a systematic literature review in uncovering research questions. The results of the study conclude that social media plays a very important role in campaigning for the government's national Covid-19 vaccination program and the form of delivery on social media using images of officials including the president plays a very important role in influencing the public to participate in the national vaccination program.